First Report on Molecular Identification of Caulerpa Green Algae from Mandangin Island Indonesia Using Partial 18SrRNA Genes - Nwet Darli Kyaw Zaw; Putu Angga Wiradana; Sin War Naw; Aondohemba Samuel Nege; Mochammad Amin Alamsjah; Rizhar Eman Karunia Akbar; Fahror Rosi (Department of Aquaculture, 2020)
Caulerpa is one of the seaweed that grows naturally in Indonesian waters such as those in Mandangin Island. This study aimed to identify Caulerpa sp. based on molecular analysis using certain genetic markers. This research is expected to provide information on the identification of macroalgae from Indonesia waters, especially Mandangin Island, Madura with the use of molecular analysis based on 18SrRNA primers. The two green seaweed samples from the Caulerpa genus in this study were successfully analyzed using 18SrRNA primers. The BLAST results of samples 1and 2 are related to Caulerpa taxifolia 18SrRNA, but in the phylogenetic tree result, Sample 1 was more closely related to Caulerpa sertularioides f. longipes. 18SrRNA primers have been used for molecular identification of green seaweed from Mandangin for the first time and this shows that barcode markers can be used for molecular identification of seaweed, specifically Caulerpa in the waters of Mandangin Island, Indonesia.